Wycena zasobów i usług środowiskowych a ekonomiczna ocena projektów gospodarczych - Kołakowski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents the valuation of environmental resources and services used in the economic evaluation of investment projects. It presents the total economic value concept and the most popular method of environmental valuation with some of their limits. Moreover the paper points to a necessity for properly using data and information, received by applying valuation methods, in the environmental cost-benefit analysis. This is also the main reason for increasing the rational decision in the economic evaluation of investment projects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 77-85